Formulation and sensory evaluation of tisanes - BENNET R,; S. VIJAYALAKSHMI,; DINESH RAJ R,; J. YUVARAJ, (International Journal of Pharma and Bio Sciences, 2016)
Tisane is a beverage infused with herbs instead of tea leaves. The main objective of the study was to formulate and analyse the herbal infusions without any tea leaves and caffeine free alternative to tea or coffee for a hot drink, to perform a sensory evaluation on 2 different herb infusions (tisanes) prepared from formulations of indigenous herbs and spices and to analyse for its biochemical and nutrient content. Tisanes infuse from product Code A- , composed of Justicia adhatoda, ocimum basilicum, Origanum vulgare, Zingiber officinale and Piper nigrum.and Code B- composed of Zingiber officinale,Piper longum, Myristica fragrans, Terminalia chebula, Nigella sativa. Thirty (30) trained panelists conducted acceptance tests on infusions from 2 formulations using 5 point hedonic scale. The mean scores of Code A and Code B were found. The highest mean score of the product Code A was further analyzed further for its biochemical andnutrient content. The mean score of the sensory attribute results showed that overall acceptability of product for the tisane Code A was slightly greater than that of tisane Code B. There was significant difference between Code A and Code B since the p value is lesser than that of t value (p<0.05). Code A was found for the presence of significant amount of poly phenol, calcium, iron and sodium. These results were confirmed it is promising that potential for introducing a consumer acceptable Code A tisane into the market.